PENGARUH PENGGUNAAN MEDIA STORYTELLING TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI - Dewi Citra Ardhana; Rasdawita Rasdawita; Agus Setyonegoro (Universitas Negeri Makassar, 2024)
This study aims to determine the effect of using storytelling media on the writing skills of descriptive text of junior high school students of SMP Negeri 19 Muaro Jambi. This research is a type of experimental research with a quasi experimentall design or a semi-experiment that uses a pretest-posttest control group design. The data obtained through the pretest and posttest scores of both groups, then the data were analyzed quantitatively with the help of the SPSS program. The results showed that the use of digital storytelling media had an influence on students' description text writing skills. The use of storytelling media can stimulate the imagination and creativity of writers by opening the door to new ideas and imaginative experiences in writing description texts.